Isolation and Determination of Fomentariol: Novel Potential Antidiabetic Drug from Fungal Material - Nevena Maljurić; Jelena Golubović; Matjaž Ravnikar; Dušan Žigon; Borut Štrukelj; Biljana Otašević (Journal of Analytical Methods in Chemistry)
Diabetes mellitus is one of the leading world’s public health problems. Therefore, it is of a huge interest to develop new antidiabetic drugs. Apart from traditional therapy of diabetes, nowadays, importance is given to natural substances with antidiabetic potential. Fomes fomentarius is a mushroom widely used for different purposes, due to its range of already confirmed activities. Fomentariol is a constituent of Fomes fomentarius, responsible for its antidiabetic potential. In that respect, it is important to develop a method for isolation and quantification of fomentariol from fungal material, which will be simple and efficient. Multistep, complex extraction applied in the previously reported studies was avoided with ethanol, providing rapid single-step extraction. The presence of fomentariol in ethanolic extract was confirmed by high-resolution mass spectrometry. Semipreparative HPLC method was developed and applied for isolation from ethanol extract and purification of the active compound fomentariol. It was a gradient reversed-phase method with a mobile phase consisting of acetonitrile and 0.1% formic acid in water and total run time of 15 minutes. The amount of 6.5 mg of high-purity fomentariol was determined by quantitative NMR with toluene as internal standard. The isolated and determined amount of substance can be further used for the quantitative estimation of activity of fomentariol.